Dificuldade do ensino de matemática: um estudo da formação docente para esta disciplina - Martinez, Ricardo Nogueira (2022)
This dissertation addresses the difficulties that exist in the teaching of mathematics, since teaching this subject often represents a great challenge for teachers and for most students who consider it complex and difficult to learn. Based on a proposal of teacher training, it discusses the possible gaps that prevent the teacher from properly training the student for the learning of this subject. Thus, the questions of this research are: can a teacher who was not qualified and who did not have adequate pedagogical training perform and teach this subject in a satisfactory way? Can this affect or not the performance of this teacher and the development of students? As a hypothesis, it is understood that both in teacher training and student learning, it is possible to teach mathematics by working the students' logical-mathematical reasoning through games. In this way, it is possible to make some changes in behavior, ultimately generating an excellent application in the teacher's class, and therefore, interest and learning for the student. In this sense, the objectives of this study are: (i) to investigate which are the greatest difficulties for teaching and learning mathematics; (ii) understand and identify at what point in the teacher's training there may have been issues that caused their bad or inadequate training, and with that, be able to propose an improvement in the teacher's teaching; (iii) propose theoretical-pedagogical interventions, which will be made in approaches to teachers as an educational consultancy, after the results of the field research. The methodology is based on the considerations of Gil (2008) and Yin (2005). It is a qualitative research, with an interdisciplinary character, including studies in the area of mathematics, according to Boyer (1996), Parra and Saiz (1996), Vitti (1999), Garbi (1997), among other authors in the educational field. The investigation was carried out through bibliographic studies and field research, with the participation of four professors and 12 students. The analysis allowed us to infer that continuous training is essential to improve mathematics teacher didactics. With this, the teacher can improve his methods to teach this discipline, optimize his class time, develop his way of teaching and evaluate more effectively, because it is a discipline that needs a lot of training and also a lot of practice by the students, it ends up becoming tiring and/or exhausting. In this sense, with good training and specialization, the teacher can make learning easier for the student to understand and, consequently, also easier for him to teach.(AU)